Path Analysis of Economic Growth and Government Spending on Education Impact on the Human Development Index in Indonesia - Lora Ekana Nainggolan; Darwin Lie; Nana Triapnita Nainggolan; Lenny Dermawan Sembiring; Acai Sudirman (Valid: Jurnal Ilmiah, 2021)
Economic development is determined by many factors, for example by the state of natural resources, human resource capabilities, and technology. Many countries are expanding references to political-economic development that still focus on the availability of their natural resources. Experience in some developed countries such as Japan and Singapore shows that the availability of natural resources is in fact not a dominant factor in political-economic development. Countries with limited natural resources have, it turns out to have a comparative advantage in the field of human resources and technology. The development of human resources needs to get dominant attention due to the limitations of its natural resources. The responsibility for development lies with the community and the government.